Discrimination of a single-item scale to measure intention to have a COVID-19 vaccine - Julius Sim; Louise E. Smith; Richard Amlôt; G. James Rubin; Nick Sevdalis; Susan M. Sherman (PLoS ONE, 2025)
Aim When developing public health measures in a pandemic, it is important to examine attitudes and beliefs relating to vaccination uptake. We report the discrimination of a single-item vaccination intention scale and derive cutpoints in terms of sensitivity (true positives) and specificity (true negatives) in relation to subsequent vaccination status. Subject and Methods In a sample of UK adults (n=1119) recruited through an online survey platform, vaccination intention was measured on a 0–10 numerical rating scale (0=very unlikely, 10=very likely) at the beginning of the UK COVID-19 vaccination rollout (January 2021), and self-reported vaccination status was gathered after vaccination had been offered to all adults (October 2021). Discrimination of the scale was measured by the area under the receiver operating characteristic (ROC) curve. Results The responders reporting being vaccinated or unvaccinated were 1034 (92.4%) and 85 (7.6%), respectively. The area under the ROC curve was.956 (95% CI.943,.967), indicating a high degree of discrimination. The combined value of sensitivity and specificity was greatest at a cutpoint of 8 on the scale (sensitivity =.821, specificity =.988). If, however, the individual values of sensitivity and specificity are required to be simultaneously optimized, this occurs at point 6 (sensitivity =.886, specificity =.871). Conclusion We recommend a 0–10 intention scale as a validated, practical measure of vaccination intention in public health practice, with a cutpoint of 8 on the scale as optimal, unless sensitivity and specificity are to be simultaneously optimized, when 6 is the optimal cutpoint.